2023
DOI: 10.3390/ijms24010740
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Auxin Response Factor (ARF) Gene Family Involved in Wood Formation and Response to Exogenous Hormone Treatment in Populus trichocarpa

Abstract: Auxin is a key regulator that virtually controls almost every aspect of plant growth and development throughout its life cycle. As the major components of auxin signaling, auxin response factors (ARFs) play crucial roles in various processes of plant growth and development. In this study, a total of 35 PtrARF genes were identified, and their phylogenetic relationships, chromosomal locations, synteny relationships, exon/intron structures, cis-elements, conserved motifs, and protein characteristics were systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
3
18
0
Order By: Relevance
“…The ARF gene was initially identified to have 23 members in the model plant Arabidopsis and has since been identified in multiple species [ 5 ]. Rice has 25 ARF members [ 11 ], apple ( Malus domestica ) has 31 ARF members [ 55 ], silver birch ( Betula pendula ) has 17 members [ 56 ], birch ( Betula platyphylla ) has 15 members [ 57 ], Euscaphis konishii has 29 members [ 26 ], and Populus has 35 members [ 12 ]. However, the ARF gene has not yet been identified in Korean pine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ARF gene was initially identified to have 23 members in the model plant Arabidopsis and has since been identified in multiple species [ 5 ]. Rice has 25 ARF members [ 11 ], apple ( Malus domestica ) has 31 ARF members [ 55 ], silver birch ( Betula pendula ) has 17 members [ 56 ], birch ( Betula platyphylla ) has 15 members [ 57 ], Euscaphis konishii has 29 members [ 26 ], and Populus has 35 members [ 12 ]. However, the ARF gene has not yet been identified in Korean pine.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in both Populus and Populus yunnanensis , which have 19 chromosomes, the ARF genes were distributed on 16 chromosomes, and the distribution of genes on different chromosomes was also uneven. Chromosome 1 was found to be the longest in both Populus and Populus yunnanensis , but it had fewer ARF genes [ 12 , 58 ]. The analysis indicated that ARF genes are distributed similarly on the chromosomes of woody plants, and the number of ARF genes on each chromosome is independent of chromosome length.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations